2016
DOI: 10.1007/s00424-016-1854-1
|View full text |Cite
|
Sign up to set email alerts
|

Cereblon in health and disease

Abstract: Cereblon (CRBN) is a substrate receptor of the E3 ubiquitin ligase complex that has been linked to autosomal recessive non-syndromic mental retardation. Several key findings suggest diverse roles of CRBN, including its regulation of the large-conductance calcium- and voltage-activated potassium (BKCa) channels, regulation of thalidomide-binding proteins, and mediation of lenalidomide treatment in multiple myeloma. Recent studies also indicate that CRBN is involved in energy metabolism and negatively regulates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 82 publications
(108 reference statements)
0
26
0
Order By: Relevance
“…As previously described, CRBN is closely associated with obesity and insulin resistance in nonalcoholic fatty liver disease models and it also regulates a variety of biological processes, including ER stress, mitochondrial biogenesis, and lipogenesis. [21][22][23] Our previous study demonstrated that the increase in CRBN by alcohol feeding exacerbated metabolic dysfunction by promoting hepatic steatosis and inflammation. 23 However, the role of CRBN in alcohol-mediated liver injury has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…As previously described, CRBN is closely associated with obesity and insulin resistance in nonalcoholic fatty liver disease models and it also regulates a variety of biological processes, including ER stress, mitochondrial biogenesis, and lipogenesis. [21][22][23] Our previous study demonstrated that the increase in CRBN by alcohol feeding exacerbated metabolic dysfunction by promoting hepatic steatosis and inflammation. 23 However, the role of CRBN in alcohol-mediated liver injury has not been investigated.…”
Section: Discussionmentioning
confidence: 98%
“…CRBN is a substrate receptor of the E3 ubiquitin ligase complex that has been associated to mild autosomal recessive nonsyndromic mental retardation. It is highly expressed in the brain and is also present in diverse tissues, including skeletal muscle, kidney, and liver . Our previous studies have demonstrated that disruption of CRBN improves hepatic steatosis and inflammation via AMPK activation in mouse models of nonalcoholic and alcoholic fatty liver diseases .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several researchers confirmed CRBN as target of lenalidomide in multiple myeloma (MM), lymphoma, chronic lymphocytic leukemia, and del(5q) MDS [48]. CRBN is the ubiquitously expressed 51 kDa protein with a putative role in cerebral development, especially memory and learning [49,50]. Our group found that del(5q) MDS patients (the so-called 5q minus syndrome) have higher levels of full-length CRBN mRNA than other patients with lower risk MDS, linking higher levels of a known lenalidomide target CRBN and del(5q) MDS subgroup known to be especially sensitive to lenalidomide [51].…”
Section: Advance In Our Understanding Of Del(5q) Myelodysplastic Syndmentioning
confidence: 99%
“…GS is important for de novo synthesis of glutamine and functions tn detoxification of glutamate and ammonia. GS is associated with diseases including cancer, Alzheimer´s disease and Huntington disease [89].…”
Section: Importance Of Valosin-containing Protein/p97 For the Degradamentioning
confidence: 99%